(untitled) (Research, Society and Development, 2020)
Use of trifoliate orange [Poncirus trifoliata (L.) Raf.] as a rootstock has intensified in recent years in Brazil. Objectives of this study were to evaluate the effects of lime and agricultural gypsum on concentration of nutrients in trifoliate orange. Seedlings of trifoliate orange were grown in PVC pipe columns, presenting 15 cm in diameter and 35 cm in length. The columns were sectioned in two rings: the upper ring, 15 cm high, and the lower ring, 20 cm high. The factorial scheme (2×4)+1 was used, being two liming treatments and four agricultural gypsum doses (carried out only in the soil of the upper ring), and an additional treatment (with liming carried out in the soil of both upper and lower ring). Liming increased Mg and S concentrations in roots of the superficial soil layer (0-15 cm). Ca concentration was higher in roots of both superficial (0-15 cm) and subsuperficial (15-35 cm) layers. Gypsum without liming resulted in higher N, K, and Mn concentrations and lower Mg concentration in roots of the soil subsurface layer. Ca and S concentrations in root of the soil superficial layer were higher with gypsum. In plant shoot, the concentrations of K, Ca, S and Cu were higher with liming, and concentrations of Ca and P were higher and lower, respectively, with gypsum application.